The Usufructuary Ethos : Power, Politics, and Environment in the Long Eighteenth Century - Drew, Erin E. (Book collections on Project MUSE., 2021)
"The Usufructuary Ethos traces an overlooked thread of environmental thought from the religious and legal writings of the seventeenth century through mid-eighteeenth-century poems of colonial commerce, attending to the particular political, economic, and environmental pressures that shaped, transformed, and ultimately sidelined it"--